Prawo do obywatelstwa jako prawo człowieka - Połatyńska, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The right to nationality is embodied in the Universal Declaration of Human Rights (1948) as one of the Human Rights granted to every human being. Although it was consequently included in several international documents, is considered to be still more like a directive of conduct for States than a legally admissible claim of an individual. By custom, it is the right of each State to determine who its nationals are. The source of that ambiguity could be found in controversies arising from the dual nature of nationality, as a legal bond between a State and an individual, recognized both in public international law and domestic law of every State.